Acts of Courage Fast Cars and Tractor Engines; Stories of Love and Hate; I'm Your Man. - Oades, Roslyn (Currency Press, 2015)
Acts of Courage forges immediacy and honesty between a vast range of Australian stories, generating forgiveness and hope in the act. Oades' unwavering loyalty to the words, sounds and silences of everyday conversations conveys a steadfast loyalty to the experiences and the people from which they come. This trilogy celebrates not only the Australian spirit through times of hardship, but everyday, extraordinary, acts of courage.